2011
DOI: 10.1667/rr2580.1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of Radiosensitive Human Cell Lines with DNA Damage Response Assays Identifies the Neutral Comet Assay as a Potential Surrogate for Clonogenic Survival

Abstract: In an effort to explore the possible causes of human radiosensitivity and identify more rapid assays for cellular radiosensitivity, we interrogated a set of assays that evaluate cellular functions involved in recognition and repair of DNA double-strand breaks: (1) neutral comet assay, (2) radiation-induced γ-H2AX focus formation, (3) the temporal kinetics of structural maintenance of chromosomes 1 phosphorylation, (4) intra-S-phase checkpoint integrity, and (5) mitochondrial respiration. We characterized a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 35 publications
(67 reference statements)
5
21
0
Order By: Relevance
“…It was also observed that the neutral comet assay provided a stronger correlation with clonogenicity at higher doses (4 Gy and 6 Gy) than at 2 Gy, which may be attributed to a lower occurrence of strand breaks at 2 Gy. For all the cell lines, the DNA repair kinetics, as measured using either neutral or alkaline comet assay, failed to strongly correlate with the radiosensitivity, which is in agreement with some of the earlier reports [24] but not with other studies [12]. Though the residual DNA damage, as measured by the neutral comet assay, is able to segregate the most radioresistant and radiosensitive cell lines, it is not able to grade all the cell types according to their radiosensitivity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was also observed that the neutral comet assay provided a stronger correlation with clonogenicity at higher doses (4 Gy and 6 Gy) than at 2 Gy, which may be attributed to a lower occurrence of strand breaks at 2 Gy. For all the cell lines, the DNA repair kinetics, as measured using either neutral or alkaline comet assay, failed to strongly correlate with the radiosensitivity, which is in agreement with some of the earlier reports [24] but not with other studies [12]. Though the residual DNA damage, as measured by the neutral comet assay, is able to segregate the most radioresistant and radiosensitive cell lines, it is not able to grade all the cell types according to their radiosensitivity.…”
Section: Discussionsupporting
confidence: 85%
“…Attempts have been made in the past to correlate DNA damage with the clonogenic survival of the tumor cells using either an alkaline or a neutral comet assay. A good correlation between DNA damage, as measured by the comet assay and clonogenic survival has been observed in some studies [10][11][12]. However, this correlation was not observed in other studies [13,14], suggesting for more number of studies in this direction for the potential application of the comet assay in determining the radiosensitivity of tumor cells.…”
Section: Introductionmentioning
confidence: 92%
“…The neutral comet assay measures the level of unrepaired DNA in a cell [14][16]. Recent studies have shown a correlation between double-strand DNA post-irradiation damage, as measured by NCA, and the colony survival assay [14].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown a correlation between double-strand DNA post-irradiation damage, as measured by NCA, and the colony survival assay [14]. Longer, undamaged DNA fragments will remain predominantly in the “head” of the comet, while smaller, heavily damaged DNA fragments will migrate more quickly and form the tail of the comet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation